The Concept of National Security in Kautilya's Arthashastra - Ghimire, Sanjay; Lamichhane, Madhav Raj (Baneshwor Campus Journal of Academia, 2024)
Kautilya's Arthashastra stands as a timeless testament to the enduring principles of political realism. Within its ancient pages, Kautilya delves into the intricate dynamics of power, conflict, and national interests with remarkable foresight. Central to his discourse is the notion of national security, a concept that remains as pertinent today as it was in antiquity. Kautilya's strategic genius is evident in his meticulous construction of military doctrines, aimed at ensuring the safety and sovereignty of the state. Through a blend of cunning diplomacy, espionage, and military prowess, he advocates for a proactive approach to safeguarding the realm against external threats and internal dissent. In the Arthashastra, Kautilya elucidates the multifaceted nature of national security, encompassing not only military strength but also economic prosperity, social stability, and ideological resilience. His realist perspective emphasizes the primacy of power dynamics in international relations, advocating for the acquisition and preservation of power as the cornerstone of national security. Kautilya's insights continue to resonate in contemporary discourse, where states grapple with complex geopolitical challenges and navigate the delicate balance between self-interest and collective security. As policymakers confront evolving threats in an increasingly interconnected world, the timeless wisdom of Kautilya serves as a beacon, offering invaluable lessons on the enduring pursuit of national security in an ever-changing global landscape.